Conversion of glucose into 5-hydroxymethylfurfural in different solvents and catalysts: Reaction kinetics and mechanism - Cunshan Zhou; Jing Zhao; Abu ElGasim A. Yagoub; Haile Ma; Xiaojie Yu; Jiali Hu; Xinjie Bao; Shulan Liu (Egyptian Journal of Petroleum)
Synthesis of 5-hydroxymethylfurfural (HMF) from glucose was done in H2O, dimethylsulfoxide (DMSO) and 1-butyl-3-methylimidazolium chloride ([Bmim]Cl) catalyzed by metal (III) chloride (FeCl3·6H2O, CrCl3·6H2O and AlCl3). The effects of solvent/catalyst system and temperature/time on the performance of the reaction are studied. HMF yield in the different solvents follows a decreasing order as DMSO > [Bmim]Cl > H2O. The highest HMF yield is achieved by CrCl3·6H2O, followed by AlCl3 and then FeCl3·6H2O. An optimal temperature/time is found at 393 K or 403 K and a time between 30 min and 480 min. Under the optimal reaction conditions, HMF yields of 54.43% and 52.86% are obtained in DMSO with CrCl3·6H2O at 403 K and 480 min and AlCl3 at 393 K and 240 min, respectively. The mechanism of the halide chlorides catalyzed glucose conversion reaction is proposed. The kinetic model is established to describe the HMF formation and the experimental data conform to the model.